Trade liberalisation in the Caribbean : survey and impact study - Lewis, David E. (Ernst & Young [S.l.])
Looks at the Caribbean trade and investment environment focusing on CARICOM and other hemispheric groupings such as the Association of Caribbean States; CARICOM and Latin America; Non-CARICOM Caribbean countries; NAFTA; FTAA-2005/WHFTS Initiative and , WTO/GATT. Examines private and public sector roles and responses.